SOA Testing Framework a framework to test your services in service-oriented development. - Krishnaswamy, Anbarasu (SOA webservices journal.)
Service oriented architecture (SOA) has become today's technology buzz and it's rapidly becoming a mainstream approach to enterprise systems design. Beyond the buzz of SOA, organizations face several challenges as they attempt to truly effectuate the paradigm shift towards SOA. One critical challenge is : How can we assure the quality of the business services that we build? Can the services we build withstand the test of rapid organizational change? One way to address this challenge is through the use of effective testing methodologies and tools for the services deployed under an organization's SOA fabric.